RETRACTED: Analisis Hukum Terkait Kerja Lembur Melebihi Batas Waktu Terhadap Hak Asasi Manusia - Nurun Isnaini (JURNAL HUKUM SEHASEN, 2023)
RETRACTION NOTICE Following up on the review of articles published in Jurnal Hukum Sehasen carefully, thoroughly, and considering the article entitled "ANALISIS HUKUM TERKAIT KERJA LEMBUR MELEBIHI BATAS WAKTU TERHADAP HAK ASASI MANUSIA" Vol 9 No 2 (2023), DOI: https://doi.org/10.37676/jhs.v9i2.4873 This paper was found to violate the publication principles of the Jurnal Hukum Sehasen and has been withdrawn.This article has been withdrawn by the Author and the article withdrawal letter is attached in PDF form.The document and its contents have been removed from the Jurnal Hukum Sehasen, and reasonable efforts should be made to remove all references to this article.